Libraries in the Digital Age, do they survive? - Dessy Harisanty; Rahma Sugihartati; Koko Srimulyo; Kathleen Lourdes Obille (International Journal of Information Science and Management)
Discourse about libraries in the digital era is widely discussed on digital media, and the existence of such discourses is the background for conducting this study. This study uses a qualitative approach using the crisis discourse analysis method by Teun A. van Dijk, which includestext, social cognition, and social context. Data crawling was conducted using the keyword "library," and 18,461 texts were found from four digital media platforms. These were filtered into 723 texts sorted based on aspects containing negative and positive perspectives of library discourse. Finally, 82 texts that could represent discourse for analysis, namely 82 texts were obtained. The results of this study found eight major discourses about libraries. This study proves that any discourse about libraries circulating on digital media is inseparable from the cognition background and social context of the creator of the discourse.